The chronoliths - Wilson, Robert Charles, 1953- (New York : Tor, 2001)
In early twenty-first-century Thailand, Scott witnesses the appearance of a two-hundred-foot stone pillar in the forest, and finds his life forever changed.
"A Tom Doherty Associates book.".
New York Times.
Pub Weekly.
Voice of Youth Advocates (V.O.Y.A.).
Adult
Keywords: Science fiction; Thailand -- Fiction; Thailand -- Fiction; Science fiction